2006
DOI: 10.1007/s10529-006-9179-3
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of polyamines in plant response to abiotic stress

Abstract: Environmental stresses are the major cause of crop loss worldwide. Polyamines are involved in plant stress responses. However, the precise role(s) of polyamine metabolism in these processes remain ill-defined. Transgenic approaches demonstrate that polyamines play essential roles in stress tolerance and open up the possibility to exploit this strategy to improve plant tolerance to multiple environmental stresses. The use of Arabidopsis as a model plant enables us to carry out global expression studies of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
344
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 524 publications
(374 citation statements)
references
References 54 publications
(50 reference statements)
9
344
0
7
Order By: Relevance
“…PAs have also been described as membrane protectors (Alcázar et al, 2006;Kusano et al, 2008), a property that is consistent with the observation that the addition of spermine dramatically inhibited H 2 O 2 -induced ion leakage in WT plants (Fig. 10B).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…PAs have also been described as membrane protectors (Alcázar et al, 2006;Kusano et al, 2008), a property that is consistent with the observation that the addition of spermine dramatically inhibited H 2 O 2 -induced ion leakage in WT plants (Fig. 10B).…”
Section: Discussionsupporting
confidence: 87%
“…7A and 7B). In plants, PAs are present as free bases or conjugated to small molecules, mainly hydroxycinnamic acids, and to various macromolecules such as proteins (Alcázar et al, 2006). It was recently suggested that there is a reverse PA pathway in plants from spermine to putrescine (Kusano et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of amino acids, especially Pro and Arg, contributes to the osmoprotection of plants (Rai, 2002). Increase in Arg content may lead to the accumulation of polyamines which protect as polycations the vital negatively charged, macromolecules in the cells (Alcázar et al, 2006). In addition, reactive oxygen species, antioxidants, amino acids and polyamines are all involved in signalling pathways which may activate further protective mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…1 They have been implicated in a wide range of biological processes, including cell growth and division, stabilization of nucleic acids and membranes, protein synthesis and chromatin function, and biotic and abiotic stresses responses. [2][3][4][5] The most common PAs are spermidine and spermine, together with their diamine precursor putrescine. The biosynthesis of PAs is controlled in plants primarily by three enzymes: arginine decarboxylase (ADC; EC 4.1.…”
Section: Introductionmentioning
confidence: 99%